A Focus Group Study of Child Nutrition Professionals' Attitudes about Food Allergies and Current Training Practices - Lee, Yee Ming; Kwon, Junehee; Sauer, Kevin L. (My University, 2016)
Purpose/Objectives: The purpose of this study was to explore child nutrition professionals' (CNPs) attitudes about food allergies, current practices of food allergy training, and operational issues related to food allergy training in school foodservice operations. Methods: Three focus groups were conducted with 21 CNPs with managerial responsibilities from a midwestern state. Responses to guided, open-ended questions were audio-recorded, transcribed verbatim, and analyzed to identify common themes. Results: Participants felt that the prevalence and types of food allergies affecting school nutrition programs have increased in recent years. They also felt that communicating with other stakeholders and verifying physicians' recommendations regarding food allergies can be difficult. Participants agreed that training could improve food allergy knowledge and awareness of their employees and improve safety of children with food allergies. However, only a few reported providing specific food allergy training for employees. Cost, scheduling difficulties, and time constraints were identified as barriers to providing food allergy training. Participants preferred having credentialed professionals to conduct employee food allergy training. Support from school administrators and witnessing a food allergic reaction in the cafeteria would trigger a decision to initiate food allergy training. Applications to Child Nutrition Professionals: Improved communication between school foodservice staff and other stakeholders is crucial to better serve students with food allergies. A well-planned, structured training program could better prepare school foodservice employees serving students with food allergies. CNPs might need continuous guidance and assistance regarding employee food allergy training. State agencies and professional organizations should work with CNPs to develop and communicate best practices for prevention and management of food allergic reactions.
Citation: Lee, Y. M., Kwon, J., & Sauer, K. (2014). A focus group study of child nutrition professionals’ attitudes about food allergies and current training practices. Journal of Child Nutrition and Management, 38(1).
Keywords: Child Nutrition Professionals; Food Allergies; Training; Attitudes; Barriers; Triggers